The impact of Community-Based Ecotourism Projects in Amboró National Park - Fabián Soria (Institute for Advanced Development Studies (INESAD), 2008)
This research examines selected Community Ecotourism projects in the Amboró National Park in Bolivia, which have been established by local environmental NGOs. The objective is to investigate the impact of these projects on the livelihoods and social relations in the communities. The main question that concerns us is if the projects have been effective in reducing or alleviating poverty and vulnerability, whilst providing environmental sustainability. The research also provides insight into the impact of the projects on social, cultural and economic structures of the communities. Furthermore, it will show whether the beneficiaries see Community Ecotourism projects as an important income and activity diversification option, and if they see the projects as environmentally sustainable. These issues can determine the final outcome of the project, and thus become decisive to evaluate if such projects can be used as a strategy to improve living conditions and reduce poverty. The research relies on interviews and data collected during fieldwork in Bolivia in July-August 2007. Four different Community Ecotourism projects in the Amboró National Park were visited, as well as key informants and stakeholders.
Keywords: Q26; Q57; 330; Ecotourism; poverty; sustainability; Bolivia